Reflecting on Studying Wicca from within the Academy and the Craft: An Autobiographical Perspective - Harrington, Melissa (The pomegranate, 2016)
This reflexive biography discusses how discovering Wicca initiated a dual learning process within the international magical community and the Academy. It describes an ongoing dynamic of personal, intellectual and spiritual development within the context of two communities, and examines perceptions and experiences of the personal, public and contested interactions of scholar and practitioner. It demonstrates the complexities of belonging to, and choosing association with, perceived communities, and how these choices influence methodological and theoretical choices in research and publishing. It highlights the dichotic and unnatural simplicity of the "insider/outsider" position, particularly within our own culture, and some of the pressures on people who identify as members of both communities. It concludes by recommending Graham Harvey's concept of "guesthood" when working with any community, and argues that in researching our own culture in our own language it is not only easy and polite to share conclusions and invite response from the researched, but recommended in order to produce work with greater depth that avoids problematical assumptions of the researcher as superior and detached. The paper also discusses the development of Pagan Studies, and how the study of contemporary Paganism is beginning to contribute new challenges, methods and tools to the academic study of religion.